Appendix to the case of the United States before the Tribunal of Arbitration to convene at Paris under the provisions of the treaty between the United States of America and Great Britain, concluded February 29, 1892 [electronic resource]. - United States. (Washington : G.P.O., 1892)
The "Appendix to the case of the United States . Volume I" is also available in: Proceedings of the Tribunal of Arbitration . Volume 2 / Bering Sea Tribunal of Arbitration, CIHM microfiche no. 14472. Tables. Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 15146-15148. At head of title: Fur-seal arbitration. "Volume I." "Russian correspondence relating to the affairs of the Russian American Company"--139 p. of documents between p. 594 and p. 595. Includes index. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44